Dampak terapi handicraft ‘meronce’ terhadap penurunan frekuensi halusinasi pendengaran - Alfianti, Ade Leta; Pratiwi, Arum (Holistik Jurnal Kesehatan, 2025)
Background: Hallucinations are a typical symptom of schizophrenia characterized by impaired sensory perception, so that sufferers will feel unreal sensations. One therapy to reduce the frequency of hallucinations is distraction by doing handicraft stringing activities, namely handicraft activities carried out by stringing or arranging materials, such as beads, seeds, or other materials using rope or thread. Purpose: To determine the effect of handicraft stringing therapy on reducing the frequency of auditory hallucinations. Method: Pre-experimental research with a before-after study design, the number of samples used was 5 patients selected through observation and interviews. The sample inclusion criteria were aged 20-59 years, hospitalized for at least 3 days in the sub-acute room, and experiencing auditory hallucinations and being cooperative. Patients were given therapy in the form of making meronce handicrafts for 3 days in 1 week with a duration of 30 minutes. Results: All patients were male, Muslim, the patient's education was elementary school to high school graduates, 3 patients were married, and 2 patients were single and worked as farmers, laborers, students, and unemployed. Paired sample test analysis, the average frequency of pre-test hallucinations was 31.60 and post-test was 23.00 with an average difference of 8.6 and a confidence level between 6.717-10.483. Conclusion: Handicraft bead therapy applied to patients with auditory hallucinations effectively helps reduce the frequency and control the recurrence of hallucinations.   Keywords: Craft Therapy; Hallucination; Hearing; Stringing; Schizophrenia.   Pendahuluan: Halusinasi adalah gejala khas skizofrenia yang ditandai dengan gangguan persepsi sensori, sehingga penderita akan merasakan sensasi yang tidak nyata. Salah satu terapi untuk menurunkan frekuensi halusinasi adalah distraksi dengan cara melakukan kegiatan handicraft meronce, yaitu kegiatan kerajinan tangan yang dilakukan dengan menyusun atau merangkai bahan-bahan, seperti manik-manik, biji-bijian, atau bahan lainnya menggunakan seutas tali atau benang. Tujuan: Untuk mengetahui dampak terapi handicraf meronce terhadap penurunan frekuensi halusinasi pendengaran. Metode: Penelitian pre-experimental dengan desain before-after study, jumlah sampel yang digunakan sebanyak 5 pasien dipilih melalui observasi dan wawancara. Kriteria inklusi sampel yaitu berusia 20-59 tahun, menjalani rawat inap minimal 3 hari di ruang subacute, dan mengalami halusinasi pendengaran dan kooperatif. Pasien diberikan terapi berupa membuat kerajinan tangan meronce selama 3 hari dalam 1 minggu dengan durasi 30 menit. Hasil: Seluruh pasien berjenis kelamin laki-laki, beragama islam, pendidikan pasien tamatan SD hingga SMA,  3 pasien berstatus menikah, dan 2 pasien lajang serta bekerja sebagai petani, buruh, pelajar dan tidak bekerja. Analisis paired sample test, rata-rata frekuensi halusinasi pre-test adalah 31.60 dan post-test adalah 23.00 dengan selisih rata-rata sebesar 8.6 dan tingkat kepercayaan antara 6.717-10.483. Simpulan: Terapi handicraft meronce yang diterapkan pada pasien dengan halusinasi pendengaran secara efektif membantu menurunkan frekuensi dan mengendalikan kekambuhan halusinasi.   Kata Kunci: Halusinasi; Meronce; Pendengaran; Skizofrenia; Terapi Handicraft.